20 Intraoperative Complications and Initial Management (Facial Reconstruction After Mohs Surgery, 2018)
This chapter discusses philosophical as well as surgical approaches to the management of complications in soft-tissue facial reconstruction. Techniques of “extreme ownership” with regard to patient care are discussed. The identification and management of intraoperative complications including fire, bronchospasm, anaphylaxis, corneal injuries, and nerve injuries are discussed with regard to both management and prevention.
Keywords: Jocko Willink; extreme ownership; complication; intraoperative fire; Bovie cautery; bronchospasm; bronchoconstriction; anaphylaxis; corneal injuries; nerve injuries